PHYLLOSILICATES IN VERY LOW-GRADE METAMORPHISM: TRANSFORMATION TO MICAS - Árkai P. (My University, 2002)
Phyllosilicates produced mostly by weathering of magmatic, metamorphic and sedimentary rocks are widespread in the surficial and near-surface zones of the Earth’s crust. These phyllosilicates display very fine grain sizes, disordered crystal structures, and greatly varying chemical compositions, and they represent structurally and chemically metasable phases. They are subjected to heat during diagenesis and concomitant metamorphism, which provides a long-life source of energy for transforming the metastable phases into thermodynamically more stable phases through a long series of partly continuous, partly discontinuous reactions. The present review summarizes some major mineralogical aspects of these processes, with special reference to petrogenetic applications. Forty years have passed since the first petrogenetic application of the illite structural changes for characterizing diagenetic processes in sedimentary basins (Weaver 1960). Weaver’s “sharpness ratio” as well as Kubler’s (1964, 1968) empirical illite “crystallinity” index, have been easy-to-use X-ray powder diffraction (XRD) measures of the manifold, inter-related changes that the hydrous, mica-like phyllosilicates experience during increasing burial. In the first two decades after the introduction of the illite “crystallinity” concept, it was applied to metamorphic petrogenetic studies in certain areas of Europe (especially to the external fold and thrust belts of the European Alps, Variscides, etc.). These studies were the starting point of important further developments which include: awareness of the phyllosilicate transformations during deep burial in sedimentary basins (Hower et al. 1976; Inoue et al. 1990; Amouric and Olives 1991; Lanson and Champion 1991; Lindgreen and Hansen 1991; Eberl 1993; Huang et al. 1993;Whitney and Velde 1993; Huggett 1995; Elliott and Matisoff 1996; Nieto et al. 1996; Dong et al. 1997), and recognition of the nature of interstratified clay minerals (see Reynolds and Hower 1970). Moreover, using the theory of powder X-ray powder diffraction (e.g., …